Inducción de mutaciones para la obtención de gramíneas ornamentales - Riccardo, María Laura; Landau, Alejandra Mabel; Facciuto, Gabriela Rosa; Bugallo, Veronica Lucia (Sociedad Argentina de Botánica, 2026)
Poster